2011
DOI: 10.1002/cjoc.201180323
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method for the Preparation of 1,5‐Diaryl‐3‐(arylamino)‐1H‐pyrrol‐2(5H)‐ones

Abstract: A simple and eco-friendly method for the preparation of 1,5-diaryl-3-(arylamino)-1H-pyrrol-2(5H)-ones via the cyclo-condensation reaction of aldehydes, amines and ethyl pyruvate in the presence of silica supported ferric chloride (SiO 2 -FeCl 3 ) as reusable heterogeneous catalyst is described. The present methodology offers several advantages such as excellent yields, simple procedure and short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…197–198 °C (lit. : 17 195–197 °C); 1 H NMR (500 MHz, CDCl 3 ) δ 7.40–7.32 (m, 2H), 7.31–7.16 (m, 6H), 7.06–7.00 (m, 2H), 6.88–6.77 (m, 4H), 6.47 (s, 1H), 5.93 (d, J = 2.6 Hz, 1H), 5.57 (d, J = 2.6 Hz, 1H), 3.77 (s, 3H), 3.74 (s, 3H). 13 C NMR (125 MHz, CDCl 3 ) δ 167.19, 156.96, 154.41, 137.67, 134.86, 132.99, 130.28, 128.89, 128.11, 126.93, 123.78, 118.46, 114.69, 114.15, 106.18, 64.76, 55.60, 55.34.…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…197–198 °C (lit. : 17 195–197 °C); 1 H NMR (500 MHz, CDCl 3 ) δ 7.40–7.32 (m, 2H), 7.31–7.16 (m, 6H), 7.06–7.00 (m, 2H), 6.88–6.77 (m, 4H), 6.47 (s, 1H), 5.93 (d, J = 2.6 Hz, 1H), 5.57 (d, J = 2.6 Hz, 1H), 3.77 (s, 3H), 3.74 (s, 3H). 13 C NMR (125 MHz, CDCl 3 ) δ 167.19, 156.96, 154.41, 137.67, 134.86, 132.99, 130.28, 128.89, 128.11, 126.93, 123.78, 118.46, 114.69, 114.15, 106.18, 64.76, 55.60, 55.34.…”
Section: Experimental Partmentioning
confidence: 99%
“…210–212 °C (lit. : 17 214–216 °C); 1 H NMR (500 MHz, CDCl 3 ) δ 7.56–7.46 (m, 2H), 7.36–7.21 (m, 8H), 7.21–7.15 (m, 2H), 7.03–6.96 (m, 2H), 6.64 (s, 1H), 6.05 (d, J = 2.6 Hz, 1H), 5.64 (d, J = 2.6 Hz, 1H); 13 C NMR (125 MHz, CDCl 3 ) δ 167.00, 139.72, 136.82, 135.72, 131.76, 130.25, 129.37, 129.21, 129.05, 128.48, 126.64, 126.20, 122.49, 117.89, 108.62, 64.21.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Dabiri and Salehi first reported that 2,3-dihydroquinazolin-4(1H)-ones could be synthesized from a novel one-pot three components condensation of isatoic anhydride, an aromatic aldehyde, and a primary amine or ammonium salts [18,19]. Since then, some other catalysts such as p-TsOH [20], acetic acid [21], Zn(PFO) 2 [22], Ga(OTf) 3 [23], ionic liquid [24,25], montmorillonite K-10 [26,27], Al(H 2 PO 4 ) 3 [28], I 2 [29,30], amberlyst-15 [31], silica sulfuric acid [32], silica-bonded S-sulfonic acid [33], Al/Al 2 O 3 and Fe 3 O 4 nanoparticles [34,35], copolymer-PTSA [36], MCM-41-SO 3 H [37], SiO 2 -FeCl 3 [38] and silica-bonded N-propylsulfamic acid [39] have also been reported. However, these methodologies suffer from at least one of the following disadvantages: long reaction time, high temperature, and costly reagents.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (400.13 MHz, CDCl 3 ): δ H : 6.32 (1H, d, 3 J HH = 2.8 Hz, CH), 6.48 (1H, d, 3 J HH = 2.8 Hz, CH), 6.70 (1H, s, NH), 6.99 (1H, t, 3 J HH = 7.6 Hz, CH Ar ), 7.09-7.14 (2H, m, CH Ar ), 7.21-7.23 (1H, m, CH Ar ), 7.28-7.35 (4H, m, CH Ar ), 7.37-7.47 (2H, m, 13 C NMR (100.6 13 C NMR (100.6 MHz, CDCl 3 ): δ C : 60.1 (CHN), 106.3, 116.7, 120.5, 121.3, 124.7, 127.0, 127.7, 129.0, 129.1, 129.4, 129.8, 132.5, 133.0, 134.7, 137.1, 141.1, 167.3 (C=O). MS: m/z [%]: 360 [100], 362 [62], 297 [75], 268 [100], 240 [100], 229 [100], 204[29], 92[17], 77[15] 1. H NMR (400.13 MHz, CDCl 3 ): δ H : 4.00 (3H, s, OCH 3 ), 6.16 (1H, d, 3 J HH = 2.8 Hz, CH), 6.26 (1H,d, 3 J HH = 2.8 Hz, CH), 6.65 (1H, s, NH), 6.81 (1H, t, 3 J 2.5.16 | 5-(2-Metoxyphenyl)-1-(p-tolyl)-3-(ptolylamino)-1,5-dihydro-2H-pyrrol-2-one (4p) White cream powder, IR (KBr): ν max 3328 (N-H), 3027 (C SP 2 -H), 2920 (C SP 3 -H), 1669 (C=O), 1535 (C=C) cm 1 H NMR (400.13 MHz, CDCl 3 ): δ H : 2.29 (3H, s, CH 3 ), 2.31 (3H, s, CH 3 ), 5.62 (1H, d, 3 J HH = 2.4 Hz, CH), 5.98 (1H, d, 3 J HH = 2.8 Hz, CH), 7.00 (2H, t, 3 J HH = 7.2 Hz, CH Ar ), 7.10-7.14 (5H, m, CH Ar + NH), 7.15-7.16 (2H, m, CH Ar ), 7.25-7.28 (2H, m, CH Ar ), 7.36 (2H, dd, 3 J HH = 6.4 Hz, 4 J HH = 2.0 Hz, CH Ar ).…”
mentioning
confidence: 99%